1-(6+x)=3-4(x-1)

Simple and best practice solution for 1-(6+x)=3-4(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-(6+x)=3-4(x-1) equation:


Simplifying
1 + -1(6 + x) = 3 + -4(x + -1)
1 + (6 * -1 + x * -1) = 3 + -4(x + -1)
1 + (-6 + -1x) = 3 + -4(x + -1)

Combine like terms: 1 + -6 = -5
-5 + -1x = 3 + -4(x + -1)

Reorder the terms:
-5 + -1x = 3 + -4(-1 + x)
-5 + -1x = 3 + (-1 * -4 + x * -4)
-5 + -1x = 3 + (4 + -4x)

Combine like terms: 3 + 4 = 7
-5 + -1x = 7 + -4x

Solving
-5 + -1x = 7 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-5 + -1x + 4x = 7 + -4x + 4x

Combine like terms: -1x + 4x = 3x
-5 + 3x = 7 + -4x + 4x

Combine like terms: -4x + 4x = 0
-5 + 3x = 7 + 0
-5 + 3x = 7

Add '5' to each side of the equation.
-5 + 5 + 3x = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 3x = 7 + 5
3x = 7 + 5

Combine like terms: 7 + 5 = 12
3x = 12

Divide each side by '3'.
x = 4

Simplifying
x = 4

See similar equations:

| a^2=a^3 | | 8x-4+5x+8=90 | | 2x+13=-95-10 | | 8x-4+5x+8=180 | | 0.25g=2 | | c+8c^3-3c^7= | | Y-8+2y=28 | | 5n-3=24 | | 8-7x=124-35x | | 2x-1/2=3x+2 | | 21-5y=56 | | -5y+21=56 | | -5y-21=56 | | 5y-21=56 | | 5y+21=56 | | 200=y+100 | | 30x^5*4x^3= | | Y/2+9=20 | | 3w+6x-14y+5w+8x+5y= | | 20+6x=150-4x | | c=zn+z | | 30x-9y=0 | | x+4/3x=10 | | 5x^2*2x^2= | | 3y-21=12x | | 45=3y-6 | | 3y=15x-12 | | 9(8c-1)-18=70c+9 | | 5x^2*2= | | 100y=400 | | -4(3x-9)=18-12x | | 4x+105=8x-11 |

Equations solver categories